Endoscopic Treatment of Obesity and Nutritional Aspects of Bariatric Endoscopy - Král, Jan; Machytka, Evžen; Horká, Veronika; Selucká, Jana; Doleček, Filip; Špičák, Julius; Kovářová, Viktorie; Haluzík, Martin; Bužga, Marek (Nutrients, 2021)
Obesity is a significant problem worldwide. Several serious diseases that decrease patient quality of life and increase mortality (high blood pressure, dyslipidaemia, type 2 diabetes etc.) are associated with obesity. Obesity treatment is a multidisciplinary and complex process that requires maximum patient compliance. Change of lifestyle is fundamental in the treatment of obesity. While pharmacotherapeutic options are available, their efficacy is limited. Surgical treatment though highly effective, carries the risk of complications and is thus indicated mostly in advanced stages of obesity. Endoscopic treatments of obesity are less invasive than surgical options, and are associated with fewer complications and nutritional deficits. Currently, there is a large spectrum of endoscopic methods based on the principles of gastric volume reduction, size restriction and gastric or small bowel bypass being explored with only few available in routine practice. The aim of this publication is to present an up-to-date summary of available endoscopic methods for the treatment of obesity focusing on their efficacy, safety and nutritional aspects.
Keywords: výsledek terapie; obezita; deficience; endoskopie trávicího systému; obesity; Bariatric Surgery; Endoscopy, Digestive System; weight loss; Humans; Nutritional Status; nutriční stav; Obesity; endoscopic bariatric and metabolic treatments (EBMTs); nutrition; Treatment Outcome; bariatrická chirurgie; lidé